BIMBINGAN TEKHNIS HIGH PERFORMANCE NUTRITION PROGRAM BAGI PELATIH CABANG OLAHRAGA DI JAKARTA - Junaidi; Tirto Apriyanto; Hidayat Humaid (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract In Indonesia, especially in Jakarta, there are many coaches who train athletes from various sports. Many of them haven’t understand the science about the High Performance Nutrition Program. Seeing this condition, we will carry out High Performance Nutrition Program training for sports coaches in DKI Jakarta, so that they have the ability to prepare the High Performance Nutrition Program menu. This training begins with problem analysis, training implementation and reporting from April 2022 to October 2022. The training activity was held at the “Jakarta High Performance Center - KONI DKI Jakarta”, on August 20, 2022 and was attended by 40 sports coaches. The method of activity is carried out through a theoretical approach consisting of material presentation, discussion, and question and answer and a practical approach consisting of the practice of preparing the High Performance Nutrition Program menu. The method of carry out activities using zoom and face-to-face applications. The output of this activity is in the form of increasing the ability of sports coaches in preparing the High Performance Nutrition Program menu. Abstrak Di Indonesia, khususnya di Jakarta banyak pelatih yang melatih atlet dari berbagai cabang olahraga, banyak yang masih kurang memahami ilmu dalam bidang High Performance Nutrition Program. Melihat kondisi ini, kami tergerak untuk mengadakan pelatihan High Performance Nutrition Program bagi pelatih cabang olahraga yang berada di DKI Jakarta agar mempunyai kemampuan melakukan penyusunan menu High Performance Nutrition Program. Pelatihan ini dimulai dengan analisa masalah, pelaksanaan pelatihan dan pembuatan laporan pada bulan april 2022 sampai bulan oktober 2022. Kegiatan pelatihan dilaksanakan di Jakarta High Performance Center - KONI DKI Jakarta, pada tanggal 20 Agustus 2022 dan diikuti 40 pelatih cabang olahraga. Metode kegiatan dilakukan melalui pendekatan teoritis yang terdiri dari pemaparan materi, diskusi, dan tanya jawab dan pendekatan praktek yang terdiri dari prektek penyusunan menu High Performance Nutrition Program. Metode pelaksanaan kegiatan dengan menggunakan aplikasi zoom dan tatap muka. Luaran dari kegiatan ini berupa peningkatan kemampuan pelatih cabang olahraga dalam penyusunan menu High Performance Nutrition Program.